Comparison of Students' Mathematics Learning Achievement on Environmental Development and Regular Pathways - HS, Ferdi Gunsan; Sutiarso, Sugeng (Universitas Wiralodra, 2023)
Based on the Bandar Lampung City Regional Regulation Number 1 of 2012 concerning the Implementation of Education which frees school fees for poor families, of course it has a very positive impact on reducing the increase in early age unemployment, but on the other hand it is possible that it can have a negative impact when the entrance test for new students is eliminated. alone will affect the achievement of student learning outcomes. Therefore the purpose of this study was to test whether there were differences in achievement in mathematics learning outcomes between students from the Affirmation/Environmental Development pathway and Regular pathway in Odd Semester for class VII SMP Negeri 12 Bandar Lampung in the 2022/2023 academic year. The research method uses a quantitative descriptive research method. The data collected was taken from the results of midterm and final semester tests processed using the two-sample Mann Whitney test formula. Based on the research results, it is known that there is no significant difference in student performance on the environmental development/affirmation track and the regular track.